The dependence of milk yield on the living weight of cows of Simmental breed - Sattarov, F.R; Ashirov, M.E; Bahriddinov, F.B. (Proceedings of The ICECRS, 2020)
Studies have found that increasing the salinity of dairy cows with Simmental breeds in the herd is important in increasing milk production and creating high-yielding herds. The amount of milk of the cows having 531-560 kg live weight with the type of milk production was 768-1153 kg (P>0,999), milk fat output was 21.6-27.9 kg, 4% milk volume was 540,3-697.1 kg) higher than the different living weight Equinox with the type of milk-meat, and these indicators were determined as 932.5-1401.3 kg), 26.9-38.5 kg.